ТР53 Codon 72 Polymorphism and Human Papilloma Virus-Associated Cervical Cancer in Kyrgyz Women - Isakova, Jainagul (Asian Pac J Cancer Prev, 2019)
BACKGROUND: The aim of this study was to ascertain the magnitude of association of gene ТР53 Arg72Pro polymorphic marker with cervical cancer (CC) in Kyrgyz women. METHODS: We identified and included 205 women of Kyrgyz ethnicity for this case-control study, of whom N=103 were women (mean age 53.5 ± 10.0 years) with histologically confirmed CC and N=102 controls (mean age 46.5 ± 8.5 years). We detected human papilloma virus (HPV) DNA types 16 and 18 using polymerase chain reaction (PCR) with hybridization/fluorescent detection. Genotypes of ТР53 gene Arg72Pro polymorphism were identified using PCR-RFLP assay. RESULTS: Eighty-eight percent (90/103) women with CC had HPV, of whom 43.4% (39/90) had HPV type 16, 24.4% (22/90) had HPV type 18, whereas 32.2% (29/90) carried both types. The univariate analysis of allele and genotype distribution of Arg72Pro polymorphic marker of ТР53 gene showed no difference between CC and control groups (χ(2)=1.24, р=0.54). However, when CC cases associated with HPV were tested against controls, Arg72 allele and Arg72Arg genotype prevalence were greater compared to controls (χ²=7.25; р=0.027 for genotypes and χ²=6.83; р=0.009 for alleles). In HPV-positive women, Arg72Arg genotype of ТР53 gene was associated with a 1.85-fold increase in the likelihood of CC (OR=1.85 [95% confidence interval (CI) 1.03-3.32]), whereas Arg72 allele increased this likelihood 1.94-fold (OR=1.94 [95% CI 1.20-3.15]). CONCLUSIONS: Arg72Arg genotype and Arg72 allele of ТР53 gene in Kyrgyz women increase the risk of HPV-associated CC.